Teachers in Distance Education During the COVID-19 Pandemic. Context of Mainstream, Inclusive and Special Education - Nieduziak, Edyta M. (International Journal of Research in E-learning, 2022)
The aim of the article is to present the results of research on distance education conducted during the COVID-19 pandemic in the Silesian Voivodeship (Poland). The research focuses on the work of teachers in mainstream schools and those who work with students with special educational needs. The author presents: the difficulties indicated by teachers, the support they experience and the solutions they apply, especially to students with special educational needs. The study was based on a quantitative paradigm, using a diagnostic survey method and online survey questionnaires, sent to respondents in the LimeServey system. 958 teachers representing primary and secondary schools participated in the study. The teachers indicated the difficulties of distance learning, such as the inability to monitor the progress of students, problems with the organization of group activities and the use of activating methods in teaching. They found the support in interpersonal contacts and self-study work; they rarely used the help of specialists. Half of the respondents worked with students with special educational needs. The largest group of such students were those with specific learning difficulties. Students with disabilities accounted for about 36% of those students identified by teachers. The teachers working with students with special educational needs experienced technical problems on the part of the student and psychophysical problems resulting from the specific condition of the student with special educational needs. The results of the research and the recommendations were presented to the school authorities in order to improve the quality of distance education and raise the standards of teachers.